Correlation Between Habit in Watching English Movies and Vocabulary Mastery of Grade VIII Students at Junior High School Palu - Sakina, Sakina; Mukrim, Mukrim; Eisenring, Moh. Abraham Akbar; Hastini, Hastini (Universitas Lancang Kuning, 2025)
The objective of this study was to determine whether there was a correlation between the habit in watching English movies and vocabulary mastery of grade eight students of SMP Negeri 2 Palu. This research used correlational design. The sample of this study was 36 students from class VIII B SMP Negeri 2 Palu. Purposive sampling was used to select the sample. The instruments used in this study were questionnaires and vocabulary tests. The Pearson Product Moment correlation method was used to correlate habit in watching English movies and vocabulary mastery. The results showed a moderate correlation between the habit in watching English movies and students' vocabulary mastery. It can be proven by the sig value obtained (2-tailed) 0.000, where this value is smaller than 0.05 so a correlation value of 0.532 is obtained. This shows that the habit of watching English movies positively impacts students' vocabulary mastery. It implies that students can implement the habit of watching English movies to improve their vocabulary mastery, the more often students watch English movies; the more students' vocabulary mastery will increase. Keywords: Habit, Movies, Vocabulary